Do as I say and do as I do? The mediating role of psychological contract fulfillment in the relationship between ethical leadership and employee extra-role performance - Ahmad, Ifzal; Donia, Magda B. L.; Khan, Asadullah; M., Waris (Emerald Publishing Limited, 2018)
Purpose: The purpose of this paper is to investigate the impact of ethical leadership on two important employee extra-role behaviors; organizational citizenship behaviors (OCBs) and creative performance (CP). Drawing on social exchange and organizational support theories, psychological contract fulfillment (PCF) was proposed as the mediating mechanism explaining this relationship. Design/methodology/approach: Data were collected via questionnaire from 248 employee-supervisor/colleague dyads employed in a large fast-moving consumer goods multinational company in Pakistan. The hypotheses were tested using structural equation modeling.